2022
DOI: 10.3390/app12020557
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Impairment of Knee Stabilizer Muscles in a COVID-19 Cluster of Female Volleyball Players: Which Role for Rehabilitation in the Post-COVID-19 Return-to-Play?

Abstract: COVID-19 athletes reported persistent and residual symptoms many weeks after initial infection, including cough, fatigue, and neuromuscular disorders. Poor neuromuscular control may cause inefficient movement strategies increasing anterior cruciate ligament load. This is particularly relevant in female athletes, who show a 3-time higher risk than male counterparts. Aim is to evaluate the impairment in thigh muscles activation, body composition, and physical performance after COVID-19 in volleyball athletes. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 72 publications
0
24
0
Order By: Relevance
“…Indeed, poor neuromuscular control may lead to inefficient movement strategies by increasing ACL loading. Accordingly, previous studies have used alternative drop jump testing protocols to analyse muscle activation of the knee stabilizers to identify a potential risk of dynamic valgus due to inadequate neuromuscular timing [ 78 , 79 ]. Reviewing jump tests other than those related to dynamic knee valgus, we found that all but one test fit into one of two categories: the first category assessed the asymmetry between legs in single-leg jumps, focusing on metrics such as jump height or width [ 18 , 39 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, poor neuromuscular control may lead to inefficient movement strategies by increasing ACL loading. Accordingly, previous studies have used alternative drop jump testing protocols to analyse muscle activation of the knee stabilizers to identify a potential risk of dynamic valgus due to inadequate neuromuscular timing [ 78 , 79 ]. Reviewing jump tests other than those related to dynamic knee valgus, we found that all but one test fit into one of two categories: the first category assessed the asymmetry between legs in single-leg jumps, focusing on metrics such as jump height or width [ 18 , 39 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the COVID-19 infection, difficulties sometimes can occur in the healthiest population, such as athletes. De Sire et al [ 38 ] examined the neuromuscular function of female volleyball players after recovering from COVID-19 and concluded that they may experience an increased risk of injury as a consequence of weak quadriceps varus/valgus stabilization during ACL stressful movements. Authors conclude that COVID-19 influenced the athletes’ body composition with weight loss, sarcopenia, and possible malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Due to contradictory reports produced by different researchers, further research is needed in this regard. However, taping can be considered as part of comprehensive rehabilitation plans for pathological conditions and injury prevention [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%